Pelatihan Dasar Pembuatan Diorama Tata Surya Dalam Pameran Pekan Ilmiah Science Exhibition di SDS Peachblossoms - Ade Nurul Hidayat; NUR ILMAN ILYAS; Dwi Irwati; Afra Nuraini; Tri Ngudi Wiyatno (Jurnal Pelita Pengabdian, 2025)
Community service is carried out by UPB industrial engineering lecturers to provide contributions and support from the campus to the community. Education is a conscious and systematic effort that guides students to obtain the ideal nature and quality of education. Education should support the physical and mental development of students until they reach adulthood. Education, both formal and informal, cannot be separated from life. Students get information and insight from teachers who act as mentors/trainers. However, because the number of students in one class is large, teachers cannot provide individual teaching. Science exhibitions at schools are a means to foster children's creativity, so teachers and students use science exhibitions as a source of information, facilities, and supporting media in the learning process. Meaningful project-based learning is one way to improve children's skills, and this event provides a lot of insight. Students can also actively participate in project implementation. Three methods are used to achieve this philanthropic goal: lectures, Q&A discussions, training, and project creation. The projects created have a positive impact on children, and receive good support from parents because the sixth grade students can create good work and can present it well.